State-Space Realization of the Wave-Radiation Force within FAST: Preprint - Duarte, T.; Sarmento, A.; Alves, M.; Jonkman, J. (National Renewable Energy Laboratory (U.S.), 2013)
Several methods have been proposed in the literature to find a state-space model for the wave-radiation forces. In this paper, four methods were compared, two in the frequency domain and two in the time domain. The frequency-response function and the impulse response of the resulting state-space models were compared against the ones derived by the numerical code WAMIT. The implementation of the state-space module within the FAST offshore wind turbine computer-aided engineering (CAE) tool was verified, comparing the results against the previously implemented numerical convolution method. The results agreed between the two methods, with a significant reduction in required computational time when using the state-space module.